Creating cartoons to represent habitual leg movements - CARLOS, Karla; CAMARGO, Eleida Pereira; MOINHO, Mayara Menezes do; SOUZA, Amanda Moraes de Paula; KUROIWA, Melissa Haruka; PRADO, Gilmar Fernandes do (Arquivos de Neuro-Psiquiatria, 2020)
Many people have a habit of moving their legs and believe that this behavior is due to the restless legs syndrome (RLS), a highly prevalent neurological condition that greatly impairs the quality of life of affected individuals. This behavioral pattern, characterized by the habit of moving one’s legs and feet, may be an important confounding factor in the diagnosis of RLS. Objective: To describe the main movements associated with this benign behavioral state to characterize a possible clinical condition that can contribute to the differential diagnosis of RLS. Methods: Experienced sleep specialists, who primarily see RLS patients listed the most frequent movements people without RLS report while describing their suspected RLS. We first compiled a list of the lower-limb movements described by the specialists. Then, one of the authors (KC) carried out all movements of the list on camera to obtain a video footage. This footage was sent to one of the authors, EPC, who, alongside a group of students, drew graphic representations (cartoons) of the recorded movements. Results: The panel of sleep experts described 13 leg movements commonly reported by their patients. The experts reported 11 simple movements and two combined movements. Conclusion: In this study we developed an instrument that allows us to oppose and distinguish a pathological condition (RLS) from a behavioral phenomenon. This state of behavioral leg fidgeting needs to be better characterized and may eventually be recognized as a clinical entity per se.
Keywords: restless legs syndrome; movement; diagnosis